Formulation and Evaluation of Sustained Release Bilayer Tablets of Losartan Potassium - Sandhya, Tera (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Heart disease is very common cause of deaths in the world. Hypertension is the most prevalent form of heart disease. Losartan has wonderful clinical effectiveness in the treatment of essential hypertension and congestive heart failure. Single dose of losartan can maintain the lowering of blood pressure up to 6–8 h. Hence, repetitive medication is required in a day to maintain the blood pressure. Hence, the aim of this work is to formulation and evaluate of sustained release (SR) bilayer tablet of losartan potassium in which the immediate release layer will release the drug within 10 min and SR layer will maintain uniform drug levels over a sustained period of time. Materials and Methods: This research work is performed for the partial fulfillment of the degree of master of pharmacy. The tablets were evaluated to thickness, hardness, diameter, weight variation, drug content uniformity, friability, and in vitro drug release studies. In vitro drug release studies were performed using USP type II apparatus (paddle method) at 50 rpm in 900 ml of 0.1N HCl as dissolution medium for first 2 h and later replacing it with 900 ml pH 6.8 phosphate buffer solution for the remaining time period at 37±0.5°C. Results: The results of Fourier transform infrared and differential scanning calorimetry analysis showed that there was no physical and chemical interaction between drug and other excipients. The stability studies of optimized formulation ME5 at 400C/75%RH for 3 months did not show any variation in the tasted parameter and release.